Determinants Of Impulse Buying On E‑Commerce Apps During Promotional Campaigns: Evidence From Lamongan - Saifuddin Zuhri; Indri Hastuti Listyawati; Galih Pratama Putra; Ghoriqna Fibahril Wahdah; Monesta Cici Ijan (International Journal of Management and Business Economics, 2026)
This study investigates the factors that influence impulse buying behavior on e‑commerce applications during online shopping campaigns in Lamongan Regency. The objective is to assess the effects of live streaming, hedonic shopping motivation, price discounts, online customer reviews, sales promotions, shopping lifestyle, perceived enjoyment, scarcity messages, and online shopping experience on consumers’ impulse purchases. A quantitative survey was administered to e‑commerce users in Lamongan Regency using purposive sampling (n = 300). Collected data were tested for validity and reliability, and analyzed using multiple regression analysis. Results show that live streaming, hedonic shopping motivation, price discounts, online customer reviews, sales promotions, perceived enjoyment, and scarcity messages exert significant positive effects on impulse buying, explaining a substantial portion of variance in impulsive purchase behavior. In contrast, shopping lifestyle and prior online shopping experience did not produce statistically significant impacts in this sample. The findings suggest that marketing strategies that combine interactive entertainment (live streaming), emotional engagement (hedonic motivation and perceived enjoyment), and economic incentives (discounts, promotions, scarcity cues) are particularly effective at triggering unplanned purchases during campaign periods. These insights contribute to digital consumer behavior literature and offer practical guidance for e‑commerce platforms and digital marketers seeking to design promotional campaigns that responsibly enhance engagement and sales.